On Free Field Realizations of W(2,2)-Modules - Adamović, D.; Radobolja, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
The aim of the paper is to study modules for the twisted Heisenberg-Virasoro algebra H at level zero as modules for the W(2,2)-algebra by using construction from [J. Pure Appl. Algebra 219 (2015), 4322-4342, arXiv:1405.1707]. We prove that the irreducible highest weight H-module is irreducible as W(2,2)-module if and only if it has a typical highest weight. Finally, we construct a screening operator acting on the Heisenberg-Virasoro vertex algebra whose kernel is exactly W(2,2) vertex algebra.